The Anti-Inflammatory and Uric Acid Lowering Effects of Si-Miao-San on Gout - Cao, Ling; Zhao, Tianyi; Xue, Yu; Xue, Luan; Chen, Yueying; Quan, Feng; Xiao, Yu; Wan, Weiguo; Han, Man; Jiang, Quan; Lu, Liwei; Zou, Hejian; et al. (Frontiers in Immunology, 2022)
Abstract Background: Si-Miao-San (SMS) is a well-known traditional Chinese medicine. This study aims to evaluate the anti-inflammatory effects of SMS on gouty arthritis and its potential mechanism of action. Methods: The effects and mechanism of SMS were evaluated in monosodium urate (MSU)-treated mice or macrophages. The expression of cytokines and PI3K/Akt was analyzed using real-time PCR and Western blotting analyses. Macrophage polarization was assessed with immunofluorescence assays, real-time PCR, and Western blotting. Mass spectrometry was used to screen the active ingredients of SMS. Results: Pretreatment with SMS ameliorated MSU-induced acute gouty arthritis in mice with increased PI3K/Akt activation and M2 macrophage polarization in the joint tissues. In vitro, SMS treatment significantly inhibited MSU-triggered inflammatory response, increased p-Akt and Arg-1 expression in macrophages, and promoted M2 macrophage polarization. These effects of SMS were inhibited when PI3K/Akt activation was blocked by LY294002 in the macrophages. Moreover, SMS significantly reduced serum uric acid levels in the hyperuricemia mice. Using mass spectrometry, the plant hormones ecdysone and estrone were detected as the potentially effective ingredients of SMS. Conclusion: SMS ameliorated MSU-induced gouty arthritis and inhibited hyperuricemia. The anti-inflammatory mechanism of SMS may exert anti-inflammatory effects by promoting M2 polarization via PI3K/Akt signaling. Ecdysone and estrone might be the potentially effective ingredients of SMS. This research may provide evidence for the application of SMS in the treatment of gout. Keywords: Gout, Hyperuricemia, Si-Miao-San, Inflammation, Uric acid